Modifying Mechanical Strength and Capillary Porosity of Portland Cement-Based Mortar Using a Biosurfactant from Pseudomonas fluorescens - Huan He; Nicolas Serres; Thierry Meylheuc; Justin T. Wynns; Françoise Feugeas (Advances in Materials Science and Engineering)
We characterized the effects of a biosurfactant derived from Pseudomonas fluorescens on slump loss, mechanical strength, capillary porosity, and bacterial colonization inside Portland cement-based mortar samples. Standard tests were used to evaluate the utility of this biosurfactant as an admixture. The addition of 1.5% biosurfactant increased the plasticity and improved the workability of fresh samples. Although compressive and flexural strengths of mortars with biosurfactant were lower than those of mortars without biosurfactant after a short curing period (28 days), the addition of biosurfactant increased the compressive strength of mortar after a long curing period (180 days), with 1% biosurfactant having the highest value. After 180 days, mortar with biosurfactant had significantly lower capillary absorption coefficient A values (P<0.05) than mortar without biosurfactant. Furthermore, the addition of biosurfactant reduced the relative abundance of the mortar-deteriorating bacterial genus Pseudomonas (phylum Proteobacteria).